Improving creative ability of base of pyramid (BOP) students in India. (June 2020) - Parikh, C.; Maddulety, K.; Meadows, CJ
Highlights: Divergent thinking training helped in improving creative ability in BOP students. English language is a barrier in ideas expression for non-English speaking students. Action research supports the belief that creativity studies need mixed-methods. Scope for socio-techno entrepreneurs to turn language challenge into opportunity. Abstract: A study was undertaken to investigate how to prepare Base of Pyramid (BOP) children in India for creativity. The quasi-experiment study involved seventy 5 th grade BOP students from two municipality schools in Mumbai, India. The training group students were given Design Thinking training spread over two action research cycles, while the control group received no intervention. The present study reports on findings from the second action research cycle during which the training group received training on divergent thinking skills—skills required for Design Thinking. The data was collected using classroom worksheets and intervention test sheets, and the objective was to find answers to how ideation took place during creative work and whether divergent thinking skills—as a part of Design Thinking training—helped in improving creative ability. The quantitative analysis of The Torrance Test of Creative Thinking (TTCT) inspired intervention test sheets indicated an overall significant difference in creative ability indicator scores of students who received intervention over those who did not. Furthermore, the significant difference was found for figural tasks but not for verbal tasks. The present study also showed how a mixed-method analysis can be useful for capturing socio-cultural elements, measuring relevant idea generation and identifying the need for different creative confidence-building strategies. The study identified language as a barrier for idea expression in the case of BOP students for whom language of instruction at school was different from language spoken at home. The study recommended socio-techno entrepreneurs to use this challenge as an opportunity for becoming stakeholders in creativity skilling for BOP students.